HUBUNGAN TINGKAT KEPUASAN DALAM PEMBERIAN PELAYANAN ANC DENGAN KETERATURAN PEMERIKSAAN KEHAMILAN DI BPS MAMLUâATUL DESA NGRAME KEC. PUNGGING MOJOKERTO - Hariyanto, Agus; Kristhanty, Mifta (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The development community is increasingly critical, service quality also in the spotlight especially for service today primarily for medical services. The size of the organizations success is determined by the level of satisfaction of service recipients. The level of customer satisfaction will affect the regularity of the examination. Services provided personnel must be qualified and have five main quality dimensions: tangible, Reability, responsiveness, assurance, and empathy. The design used in this study is analytic with cross sectional approach. The population of all pregnant women antenatal check as many as 45 people to obtain a sample of 32 pregnant women trimester II and III are taken by purposive sampling. The data were taken using a questionnaire. Once the data is collected and the data processing performed by using the Spearman test. Results showed ρ (value) (0,005) <value α (0.05) so that it can be interpreted that H0 is rejected dn H1 accepted meaning there is a relationship between the level of satisfaction with prenatal care regularity. High levels of education may also affect awareness of pregnant women in antenatal care on a regular basis, this is a good effect on the absorption of health education provided by the health workers. Pregnant women who regularly carry out checks in early pregnancy can be known if there is a problem in pregnancy.Keywords: Satisfaction, Regularity, Examination Pregnancy